RANCANG BANGUN ALAT UKUR GAYA DORONG DAN MOMEN UNTUK PROPELER UAV KECIL: KAJIAN SUBSISTEM - Wibowo, Singgih Satrio; Luthfi, Mochammad; Rosalia, Citra Asti (Jurnal Teknologi Terapan, 2025)
Thrust and Moment Meter (TMM) is an instrument for measuring thrust and moment or torque produced by a small electric propulsion system, which is usually used on Unmanned Aerial Vehicles (UAV) and/or small size Radio Control (RC) aircraft. This tool is designed with low-cost materials and simple process, namely Acrylonitrile Butadiene Styrene (ABS) plastic using 3D printing technology. The main component of this device is an Arduino Nano microcontroller, equipped with three Load Cell sensors and one LCD screen. The results of this research are that the TMM tool has been successfully created and tested for accuracy in several cases, and very good results were obtained where the force measurement accuracy was more than 99% (error < 1%).